The Housing Boom and Bust: Model Meets Evidence - Kaplan, Greg; Mitman, Kurt; Violante, Giovanni L. (Journal of Political Economy, 2020)
We build a model of the U.S. economy with multiple aggregate shocks (income, housing finance conditions, and beliefs about future housing demand) that generate fluctuations in equilibrium house prices. Through a series of counterfactual experiments, we study the housing boom and bust around the Great Recession and obtain three main results. First, we find that the main driver of movements in house prices and rents was a shift in beliefs. Shifts in credit conditions do not move house prices but are important for the dynamics of home ownership, leverage, and foreclosures. The role of housing rental markets and long-term mortgages in alleviating credit constraints is central to these findings. Second, our model suggests that the boom-bust in house prices explains half of the corresponding swings in non-durable expenditures and that the transmission mechanism is a wealth effect through household balance sheets. Third, we find that a large-scale debt forgiveness program would have done little to temper the collapse of house prices and expenditures, but would have dramatically reduced foreclosures and induced a small, but persistent, increase in consumption during the recovery.